2019
DOI: 10.1002/cncr.32594
|View full text |Cite
|
Sign up to set email alerts
|

Geographic disparities in residential proximity to colorectal and cervical cancer care providers

Abstract: Background Persistent rural‐urban disparities for colorectal and cervical cancers raise concerns regarding access to treatment providers. To the authors knowledge, little is known regarding rural‐urban differences in residential proximity to cancer specialists. Methods Using the 2018 Physician Compare data concerning physician practice locations and the 2012 to 2016 American Community Survey, the current study estimated the driving distance from each residential zip code tabulation area (ZCTA) centroid to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 31 publications
(76 reference statements)
3
47
0
Order By: Relevance
“…In general, disparities in survival rates by geographic area of residence at diagnosis among AYAs could arise at several points along the pathway from symptoms, to diagnosis, to treatment, to cure, remission, or death and may depend on cancer type 35,37,38 . Diagnosis delays that ultimately impact treatment efficacy and cure could arise for several reasons, including: low cancer suspicion among both AYA patients and providers because of its rarity, greater health care avoidance among rural than urban residents, 9,39 difficulties in accessing a specialist in rural areas, 40‐44 lower rates of insurance among rural than among metro and urban residents, 45,46 and employment barriers to access (eg, loss of income needed to seek care 44 ). Once the diagnosis is made, there may be delays in starting treatment because of provider availability, insurance issues, the need to take time off from employment, and the need to travel for treatment 44,47,48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, disparities in survival rates by geographic area of residence at diagnosis among AYAs could arise at several points along the pathway from symptoms, to diagnosis, to treatment, to cure, remission, or death and may depend on cancer type 35,37,38 . Diagnosis delays that ultimately impact treatment efficacy and cure could arise for several reasons, including: low cancer suspicion among both AYA patients and providers because of its rarity, greater health care avoidance among rural than urban residents, 9,39 difficulties in accessing a specialist in rural areas, 40‐44 lower rates of insurance among rural than among metro and urban residents, 45,46 and employment barriers to access (eg, loss of income needed to seek care 44 ). Once the diagnosis is made, there may be delays in starting treatment because of provider availability, insurance issues, the need to take time off from employment, and the need to travel for treatment 44,47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Cancer October 1, 2021 in rural areas, [40][41][42][43][44] lower rates of insurance among rural than among metro and urban residents, 45,46 and employment barriers to access (eg, loss of income needed to seek care 44 ). Once the diagnosis is made, there may be delays in starting treatment because of provider availability, insurance issues, the need to take time off from employment, and the need to travel for treatment.…”
Section: Cancer October 1 2021mentioning
confidence: 99%
“…In contrast, the role of residential area and geographical location has just recently come into focus. Recent studies reported impaired access to laparoscopic surgery for diverticular disease and colorectal cancer [40][41][42] as well as modern surgical oncological care for patients living in rural areas in the US [43]. However, little is known how differences in residential areas within other countries influence surgical practice.…”
Section: Discussionmentioning
confidence: 99%
“…They also have higher incidence rates of cancers that have mechanisms for primary and secondary prevention, such as lung, colorectal, and human papillomavirus-associated cancers (3). Factors that contribute to these disparities include high rates of poverty, lack of health insurance, and lack of access to primary and specialty care (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%